Meningkatkan Kemampuan Minat Membaca, Menulis, dan Berhitung (CALISTUNG) Serta Sosialisasi Penerapan Etika dan Moral - Ira Revina; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2023)
Reading, writing and arithmetic are important aspects in elementary school. Students must master the aspects of reading, writing and arithmetic. These aspects of learning have a very important role, because by reading, writing and arithmetic children can learn various ways to improve their knowledge. In addition, in everyday life academic ability is not enough to achieve success in education, but ethics and morals also need to be applied, therefore, in addition to improving calistung abilities. I also provide socialization regarding the application of ethics and morals to students. Ethics and morals are one of the problems of education, especially elementary schools which are one of the contributors to problems in this country, how can it not be, students often encounter lies about what they have done, such as fighting, low respect for parents and teachers, impolite words in communication. The process of providing this assistance will be carried out through PKL I activities by creating a program. Activities will be carried out using the group work method which consists of stages, Assessment, Planning, Intervention, Evaluation, and Termination. The final result of this program was declared successful, as can be seen from the significant changes in the students, namely starting from the students getting better trained in reading, writing, and arithmetic (calistung).